The intersection between “obvious” and “catalyzed public” through the mediating domain of civic cultures - Murru, Maria Francesca (2013)
The paper intends to analyze how the new forms of interaction and engagement allowed by the interactive and participative online technologies can help to foster empowering civic practices. It develops a theoretical reflection on the potential intersections areas between audiences, thought as the “persona ficta” (Dayan, 2005) that emerges in the role of enacting attention towards an external performance, and the public, thought as a collective entity that calls external attention and contains a fundamental orientation to shared and consensual action. It will be argued that in order to analyze the co-presence and potential overlapping between these two collectivities, it is necessary to adopt the concepts of “mediation” (Silverstone, 1999) and “civic cultures” (Dahlgren, 2009). The paper will develop this hypothesis though the empirical analysis of a case study focused on Beppegrillo.it, an Italian weblog acting as a communicative platform for the development of a civic and political movement.